PENGARUH WAKTU DAN KECEPATAN ALIRAN UDARA TERHADAP KADAR AIR PADA PROSES PENGASAPAN IKAN DENGAN SISTEM SIRKULASI ASAP BEBAS TAR - Aswan, Arizal (KINETIKA, 2018)
Coconut shell is one of the biomass that is often thrown away in traditional markets. Though coconut shell can be used as raw material to be processed into charcoal. The content of phenol in the coconut shell plays a role to preserve food naturally. One of the foods that can be preserved with the smoke produced from the coconut shell is smoked fish. But the processing is still traditionally. So therefore, the purpose of this research is to obtain a set of smokers with an environmentally friendly smoke circulation system and reduce the tar content generated from smoke to improve the quality and quantity of the product. This research uses lais fish as raw material and coconut shell as fumigation fuel. The curing temperature is maintained between 80–100 oC for 7-9 hours. Measured data include temperature, time, humidity of the fuming chamber, airflow velocity, fish weight, initial and final fuel weight, and moisture content of the starting and ending fumes. The results of the analysis of this research indicate that temperature, curing time, and airflow rate are the main factors that greatly affect the final mass of fish and the percentage of moisture content during fumigation. Where the average water content lost is 40.1% at 7 hours, 40.7% at 8 hours, and 41.3% at 9 hours.